Pemetaan Gen Resistensi Lapang terhadap Penyakit Hawar Daun Kentang pada Populasi Fl Solanum tuberosum (SH2988) x Solanum microdontum (MCD167) - J. M. Tutupary; Gustav A. Wattimena; Hajrial Aswidinnoor; , Muladno (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2004)
Potatoes can be severely affected by late blight, a fungal disease caused by Phvtophthora infestans. which can destroy the foliage and tubers of the crop. Initial attempts to control late blight in potato deployed resistance genes (R genes) derived from the hexaploid Solanum demissum (RI - Rll). However, their immunity reaction can be easily overcome by the development of new virulent factors. It is currently accepted that the most effective solution against late blight involve the use offield-resistant varieties as part of an integrated pest management strategy. Field resistance to Phvtophthora i!!festans were examined in a diploid segregating potato population. The population produced crosses between Solanum microdontum genotype (MCDI67) and tuberosum genotype (SH2988) have been assessed for resistance to f.. infestans (late blight) in the field and prol1ed to segregate for f.. infestans resistance. A genetic linkage map of this population was constructed by using PCR-based CAPS markers. The result showed that one QTL on foliage resistance to late blight were linked with marker GP 180 on chromosome 4 of potato in coupling phase. Key words: CAPS markers, Field resistance, Late blight, Phvtophthora infestans. potato, QTL